THE EFFECTS OF INTERMEDIATE CARE REHABILITATION PROGRAMS ON THE ABILITY OF HIP FRACTURE PATIENTS TO PERFORM DAILY ACTIVITIES WITH REMOTE FOLLOW-UP - Uthaekul, Anchalika; Sawayawisuth, Kittisak; Pitiruagsit, Lapassakarn; Ingkatacha, Onwaree; Polyotha, Kamonmarl (Journal of Social Science and Cultural, 2024)
The objective of this study was to compare the effects of intermediate rehabilitation programs on the ability of patients with hip fractures to perform daily activities. The study used rehabilitation programs combined with remote follow-up. The sample consisted of 60 elderly patients with hip fractures who were admitted to Nang Rong Hospital. The sample was divided into two groups using simple random sampling: the experimental group, which participated in the rehabilitation program combined with remote follow-up, and the control group, which participated in the rehabilitation program only. The research tools used were a daily activity assessment tool with a reliability of 0.9 and rehabilitation programs. The results showed that both groups of samples had a higher incidence of intertrochanteric femur fractures than neck of femur fractures, accounting for 63.3%. When comparing the daily activity assessments of the experimental and control groups before and after the experiment, it was found that the daily activity scores of both groups increased significantly at p < .05. When comparing the daily activity assessments between the experimental and control groups, it was found that the experimental group had better daily activity ability than the control group, with a statistically significant difference at p < .05. In conclusion, patients who participated in rehabilitation programs combined with remote follow-up regularly had better daily activity ability than patients who participated in rehabilitation programs only.